MENGEMBANGKAN KARAKTER ANAK SEJAK DINI BERDASARKAN PRINSIP PENDIDIKAN KARAKTER - Farhatin Masruroh (Fakultas Tarbiyah, Universitas Ibrahimy, 2017)
Character education is the main foundation to increase the human dignity. The good characters are well formed from an early age, which is when the potential of children grow rapidly. In the character building of children, parents and teachers have a very significant role. Therefore, the parents and the teachers should be the good example (uswatun hasanah) in that character building. Character is the values of human behavior that must be build through sustainable development process, including knowing the good, loving the good, desairing the good and acting the good.